Assessing house prices in Germany: Evidence from an estimated stock-flow model using regional data - Florian Kajuth; Thomas A. Knetsch; Nicolas Pinkwart (Deutsche Bundesbank, 2013)
Based on a stock-flow model of the housing market we estimate the relationship of house prices and explanatory macroeconomic variables in Germany using a regional panel dataset for 402 administrative districts. Using regional data exploits the variation across local housing markets and overcomes time-series data limitations. We take the regression residuals as a measure for deviations of actual house prices from their fundamental equilibrium level. The model specification allows to aggregate district-level residuals for various regional subsets. During the past two years for Germany as a whole single-family house prices appeared to be in line with their fundamental equilibrium level, whereas apartment prices significantly exceeded the fundamental price suggested by the model. The overvaluation of apartments is higher in towns and cities and most pronounced in the major seven cities, while single-family houses in cities appear to be only moderately above their fundamental levels.
Keywords: E32; R21; R31; 330; fundamental house prices; regional house prices; housing demand and supply